INVESTIGATING STUDENTS’ FEEDBACK TOWARD SPEAKING MATERIAL BASED ON CAPCUT APPS IN TEACHING TEXTBOOK OF MERDEKA KURIKULUM - NAFSIAH, NAFSIAH; HERYATUN, YAYU; ANITA, ANITA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This article Investigates the feedback of students toward Capcut application for Extensive Speaking. It is assumed that speaking is a difficult skill to do since for EFL recognized it as undaily spoken. In this article, the author wants to find students' feedback on the apps after the author give them how to design personal speaking video in Capcut. This research is mixed method by using the interview and survey as the method in collecting data. Hence, fIve students became the sample in this research. Besides that, the author also provides the observation as the supporting data to look on how the student engage with the apps. The data were taken from a school in Pamayaran, Banten province. This. It makes the proper subject to collect the data from these students. The findings demonstrate that the Cacput apps give students a new lease on life in terms of motivation, Confidence, and Creativity.